2008
DOI: 10.1063/1.2832505
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo analysis of noise spectra in self-switching nanodiodes

Abstract: By means of a semiclassical two-dimensional Monte Carlo technique, we analyze current noise spectra of InAlAs/ InGaAs-based submicron self-switching diodes. Shot noise ͑at low bias͒ and diffusion noise in the series resistance ͑at high bias͒ are found to dominate the current noise at low frequency ͑in the plateau beyond the 1 / f range͒. Two peaks of different origins, which may limit the device performance, are found in the noise spectra at higher frequencies. The dependence of the amplitude and frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 15 publications
0
24
0
4
Order By: Relevance
“…27 As a result, the channel current would be enhanced at low temperature. Note that the I-V characteristic of the simulated is not precisely consistent with the measured results for two reasons: (1) the surface charge density 24 is difficult to measurement and could be set by experience approximately; (2) the model is itself based on some simplifying assumptions 25 mentioned previously. These factors may be account for the discrepancy between the simulation and the experiment.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…27 As a result, the channel current would be enhanced at low temperature. Note that the I-V characteristic of the simulated is not precisely consistent with the measured results for two reasons: (1) the surface charge density 24 is difficult to measurement and could be set by experience approximately; (2) the model is itself based on some simplifying assumptions 25 mentioned previously. These factors may be account for the discrepancy between the simulation and the experiment.…”
Section: Resultsmentioning
confidence: 96%
“…The electrical MC simulations [23][24][25] of the device had shown that the rectifying characteristics of the device can be realized. The main simulated current-voltage (I-V ) results of device are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MC models have been proved to be quite useful for the analysis of the static, dynamic and noise behavior of SSDs [8,[11][12][13]. In this work we will analyze the high-frequency behavior of SSDs operating as detectors by means of MC simulations.…”
mentioning
confidence: 99%
“…This noise process has been identified as the dominating process for unbiased selfswitching nanochannels. [31][32][33] A first estimation of the noise-equivalent power (NEP) expected from these devices can be obtained by using the equation: 6 …”
Section: B Diode-like Behavior and DC Power Generationmentioning
confidence: 99%